THE ESSENCE AND CONTENT OF ISLAMIC EDUCATION IN THE REPUBLIC OF KAZAKHSTAN: THEORETICAL AND METHODOLOGICAL FOUNDATIONS - Seitakhmetova, N.L.; Kussainov, D.U.; Ayupova, Z.K.; Kuttybekkyzy, G.; Nurov, M.M. (Scientific Journal of Pedagogy and Economics, 2020)
Islamic education is the component of the educational process in post secular society, because the post secularity today acquires another sense than in the last century. Post secularity as the continuation of the secular process in the modern historical, sociocultural and political processes was found as an epoch, involving the secular educational projects in the modern time. If in the past century theology education was distanced from pragmatism of the secular educational practices, finding them too utilitarian and maintenance of man in the world; today theologies, designing the religious education, enter the modern scientific secular dialogues in the standardized programs of education. Criticism of the secular education was related to the problem of crisis of the western thinking. The well-known thinkers of the West declared about this crisis.